What does wafna mean? Towards the reception of a medieval Latin song, “Ego sum abbas Cucaniensis…”, in English-language literature - N. M. Dolgorukova; D. A. Strizhkova; K. V. Babenko (Шаги)
Our article is devoted to a detailed historical, linguistic, and cultural commentary and a new Russian translation of the song “Ego sum abbas Cucaniensis” from Carmina Burana, a Latin-German manuscript written in the first quarter of the 13th century. Our research presents an analysis of the topoi and allusions to sacred texts found in this drinking song; it also explores the context of its creation. This song provides the first mention of the fabulous and paradisiacal land of Cockaigne, an imaginary place of extreme luxury and ease where physical comforts and pleasures are always immediately at hand. In the song the abbot wins a gambling game, and the loser exclaims wafna. The word wafna is a hapax, probably of a German origin, and, according to different scholars and medievalists, it may have different meanings. Due to this mysterious exclamation, “Ego sum abbas Cucaniensis” is frequently reflected in English literature: in the 20th and 21st centuries different authors belonging to “popular” and “high” culture have used this word in their texts. However, in their works the word wafna did not fully correlate with its original meaning, but instead, due to its unique use in the above context, became a kind of marker of “goliardic” themes (primarily in connection with gambling and alcohol). There are several reasons for this. To begin with, the song’s popularity in the English-speaking environment (while apparently not being widely disseminated in the Middle Ages) is explained by the fact that it was among the first translations of poems from Carmina Burana into English by J. A. Symonds in 1884; later, in 1935–1936, it was included in Carl Orff’s cantata by the same name, texts from which were subsequently often read in schools and universities in Latin classes. Moreover, Symonds leaves the word wafna untranslated, which encourages readers to seek their own interpretations and create their own associations, just as English-language writers of subsequent eras continue to do.